Case Report: Next Generation Sequencing in Clinical Practice–A Real Tool for Ending the Protracted Diagnostic Odyssey - Limonova, Alena S.; Ershova, Alexandra I.; Meshkov, Alexey N.; Kiseleva, Anna V.; Divashuk, Mikhail G.; Kurkina, Marina V.; Drapkina, Oxana M. (Frontiers in Cardiovascular Medicine, 2022)
We report a case of sitosterolemia, which is a rare genetic disease, characterized by increased plant sterol absorption and great heterogeneity of clinical manifestations. Our patient was initially referred to the lipid clinic due to high cholesterol level and premature cardiovascular disease. Diagnosis of familial hypercholesterolemia was established in accordance with the Dutch Lipid Clinic Network criteria. Next generation sequencing was later performed, which revealed a nonsense mutation in the ABCG8 gene, which led to the diagnosis of sitosterolemia. The aim of our report is to demonstrate, how genetic testing helped to make the correct diagnosis, and to explain many of the patient’s health problems, which etiology remained unclear for many years.